5-HT3 Receptor Brain-Type B-Subunits are Differentially Expressed in Heterologous Systems - Corradi, Jeremias (2015)
Genes for five different 5-HT 3 receptor subunits have been identified. Most of the subunits have multiple isoforms, but two isoforms of the B subunits, brain-type 1 (Br1) and brain-type 2 (Br2) are of particular interest as they appear to be abundantly expressed in human brain, where 5-HT3B subunit RNA consists of approximately 75% 5-HT3Br2, 24% 5-HT3Br1, and <1% 5-HT3B. Here we use two-electrode voltage-clamp, radioligand binding, fluorescence, whole cell, and single channel patch-clamp studies to characterize the roles of 5-HT3Br1 and 5-HT3Br2 subunits on function and pharmacology in heterologously expressed 5-HT 3 receptors. The data show that the 5-HT3Br1 transcriptional variant, when coexpressed with 5-HT3A subunits, alters the EC 50 , n H , and single channel conductance of the 5-HT 3 receptor, but has no effect on the potency of competitive antagonists; thus, 5-HT 3 ABr1 receptors have the same characteristics as 5-HT 3 AB receptors. There were some differences in the shapes of 5-HT 3 AB and 5-HT 3 ABr1 receptor responses, which were likely due to a greater proportion of homomeric 5-HT 3 A versus heteromeric 5-HT 3 ABr1 receptors in the latter, as expression of the 5-HT3Br1 compared to the 5-HT3B subunit is less efficient. Conversely, the 5-HT3Br2 subunit does not appear to form functional channels with the 5-HT3A subunit in either oocytes or HEK293 cells, and the role of this subunit is yet to be determined.